2007
DOI: 10.1016/j.cell.2007.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specificity of a Hox Protein Mediated by the Recognition of Minor Groove Structure

Abstract: The recognition of specific DNA-binding sites by transcription factors is a critical yet poorly understood step in the control of gene expression. Members of the Hox family of transcription factors bind DNA by making nearly identical major groove contacts via the recognition helices of their homeodomains. In vivo specificity, however, often depends on extended and unstructured regions that link Hox homeodomains to a DNA-bound cofactor, Extradenticle (Exd). Using a combination of structure determination, comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
485
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(510 citation statements)
references
References 60 publications
(89 reference statements)
25
485
0
Order By: Relevance
“…In all four structures the trajectory of the DNA backbone deviates from B-form DNA at the core GA base step within the Exd/Pbx1 binding site. This base step is critical for Exd/Pbx1 binding as observed in the crystal structure (32)(33)(34)(35) as well as our own comprehensive CSI microarray studies (46).…”
Section: Dna Groove Dimensions In Hox-exd/pbx1 Structuresmentioning
confidence: 74%
See 2 more Smart Citations
“…In all four structures the trajectory of the DNA backbone deviates from B-form DNA at the core GA base step within the Exd/Pbx1 binding site. This base step is critical for Exd/Pbx1 binding as observed in the crystal structure (32)(33)(34)(35) as well as our own comprehensive CSI microarray studies (46).…”
Section: Dna Groove Dimensions In Hox-exd/pbx1 Structuresmentioning
confidence: 74%
“…The premise is further supported by the fact that simply decreasing conformational flexure of the Exd binding site, as would happen as a result of polyamide binding in the Inverse register, does not enhance binding to the same degree as it does when the Dp tail is in close proximity of the GA base step. The effect of minor groove located charges in Hox-three amino acid loop extension homeodomain (TALE) complexes has been borne out in structural studies of Scr-Exd-DNA complexes, where a minor groove bound arginine from Scr has been correlated with allosteric Scr-Exd interactions (35). However the studies with Scr posited that this effect was due to pre-existing DNA conformational preferences between different DNAs.…”
Section: Rationale For the Allosteric Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of Exd/Hth cofactors conferring additional specificity provided one new element of response (9). Also, the spacing specific residues located in the N-terminal arm of the HD also contribute to Hox specificity (25). Other nuclear partners, generating different combinations of HOX transcription factor complexes integrating a variety of positional cues, generate the specificity and versatility required for context-dependent Hox function (8,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have revealed that the specific regulation of fork head (fkh) by Sex combs reduced (Scr) occurs through the recognition of a specific DNA structure that is itself dependent on the nucleotide sequence [16]. Using a high throughput approach based on systematic evolution of ligands by exponential enrichment and massively parallel sequencing (SELEX-seq) to define preferential DNA-binding sites, it was shown that this mode of recognition also applied to all other Drosophila Hox/PBC complexes [10].…”
Section: Introductionmentioning
confidence: 99%